Self‐Powered UV Dual‐Band Photodetector Based on Cs3BiCl6/GaN Heterojunction for Logical Operation and Encrypted Photo‐Communication - Jingli Ma; Fei Zhang; Yakun Xing; Huifang Jiang; Yongtao Tian; Huifang Ji; Xu Chen; Di Wu; Longhui Zeng; Xinjian Li; Chongxin Shan; Zhifeng Shi (Advanced Science)
Abstract Dual‐band photodetectors have huge potential for application in secure optical communication, multicolor imaging, and logical operation. However, the majority of currently documented dual‐band photodetectors suffer from high energy consumption and poor photoresponse performance; especially, the dual‐band photodetectors targeted at the UV region have yet not been reported. In this study, for the first time, a self‐powered UV dual‐band photodetector based on Cs3BiCl6/GaN heterojunction is designed and fabricated through a dual‐source co‐evaporation technique. Experiments and theoretical simulations confirm that the unique dual‐band absorption characteristics of Cs3BiCl6 and the strong surface‐charge recombination near the Cs3BiCl6 surface are the primary factors enabling the achievement of UV dual‐band photodetection. Importantly, owing to the well‐matched energy band alignment of Cs3BiCl6 and GaN, the photodetectors exhibit ultra‐high Ion/Ioff ratio (1 × 107), large specific detectivity (1.23 × 1012 Jones), and ultrafast response speed (τr/τf = 28 µs/190 µs). Finally, utilizing the UV dual‐band characteristics of the fabricated device, the logical operation and encrypted photo‐communication applications are successfully demonstrated. The obtained results suggest that the lead‐free perovskite Cs3BiCl6 is potentially an attractive candidate for the manufacture of high‐performance UV dual‐band photodetectors that can be employed in advanced encryption technology.